Silica, Soil and Paddy Plant Productivity - Qurrohman, Budy Frasetya Taufik; Suriadikusumah, Abraham; Joy, Benny; Sudirja, Rija (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
The element Si is a functional nutrient for rice plants. The loss of available Si from paddy fields every time of harvest is relatively high. The impact of reduced available Si content is a decrease in the efficiency of N, P, K fertilization, plant resistance to abiotic and biotic stresses. Si fertilization on paddy plants in Indonesia has not been implemented massively by farmers. Si fertilization by returning rice straw and husks to the paddy field in compost and biochar is a strategic and economical step to replenish the depleted Si reserves of paddy fields. The response of Si fertilization between one region will differ depending on the concentration of Si-available in the paddy soil. The development of the critical limit of Si available for paddy soil in Indonesia needs to be investigated further so that the critical limit of Si can be used as a standard in determining the need for Si fertilization.